2014
DOI: 10.1002/2013wr015206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil properties on peat erosion and suspended sediment delivery in drained peatlands

Abstract: Erosion from peat extraction areas is known to cause siltation of water courses and poor water quality. However, the main soil parameters affecting peat erosion and suspended sediment (SS) yields from different catchments are not well understood. This paper used peat properties (degree of humification, peat type, ash content, porosity, moisture content, bulk density, and shear strength) and novel erosion threshold measurements from intact soil cores to explain peat erodibility and spatial variations in SS conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…Hence, estimation of erosion may be needed as a complementary approach for the prediction of TP export from peat extraction sites and other similar peatlands. In an earlier study on erosion and SS transport, we identified peat degree of humification (positive correlation) and particle size distribution of mineral soil beds in ditch networks as the most promising predictors of runoff SSC [ Tuukkanen et al ., ]. However, it seems that degree of humification cannot replace SSC in predicting TP concentrations because of its potentially contrasting effects on soluble and particulate P transport (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, estimation of erosion may be needed as a complementary approach for the prediction of TP export from peat extraction sites and other similar peatlands. In an earlier study on erosion and SS transport, we identified peat degree of humification (positive correlation) and particle size distribution of mineral soil beds in ditch networks as the most promising predictors of runoff SSC [ Tuukkanen et al ., ]. However, it seems that degree of humification cannot replace SSC in predicting TP concentrations because of its potentially contrasting effects on soluble and particulate P transport (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of P to mineral soil particle surfaces was probably of less importance in our study areas, as a result of very low inorganic matter content (high LOI) in the peat profiles (Table 2). Mineral soils underlying peat soil are exposed in some of these catchments [Tuukkanen et al, 2014], but their impact on P sorption could not be assessed in this study. The negative relationship obtained between degree of humification and mean runoff TP concentration (on factors 2 and 4), which was analogous to results obtained for runoff TN concentration (equation (4)), can be attributed to presumably higher P mineralization rate in less decomposed peat [Bridgham et al, 1998].…”
Section: Phosphorus Leaching From Peat Extraction Areasmentioning
confidence: 99%
“…Over the past decades, changes in peatlands hydrology and ecology has grown considerably (Erwin, 2009). In most cas-es this phenomenon is the effect of strong human impact such as drainage, peat extraction (Tuukkanen et al, 2014), forestry (Glina et al, 2016b) or agricultural use of peatlands (Limpens et al, 2008;Glina et al, 2016a). In the Middle and Western Europe, up to 90% of natural peatlands were strongly influenced by human impact during the last century.…”
Section: Introductionmentioning
confidence: 99%
“…In Ditch A, the TLS-derived net change (Figure 7a) was in favor of deposition +0.01…+0.02 dm 3 m À1 d À1 but the statistically significant net change (Figure 8a) was negligible. Erosion risk in moderately decomposed peat, such as in Koivupuro, is low because the most decomposed part of the peat erodes first and leaves behind a coarse armor of poorly decomposed peat fibers with a lower risk of erosion (Tuukkanen et al, 2014). Erosion risk in moderately decomposed peat, such as in Koivupuro, is low because the most decomposed part of the peat erodes first and leaves behind a coarse armor of poorly decomposed peat fibers with a lower risk of erosion (Tuukkanen et al, 2014).…”
Section: Estimation Of Net Erosion and Deposition From Surface Topogrmentioning
confidence: 99%